The Extent To Which News Directors At The Jordan Radio And Television Corporation Adhere To International Media Standards And The Effect Of That On The Accuracy Of The Media News - Ibrahim Mohammad Abdullah AlBreizat; Wesam Almahallawi; Suria Hani A. Rahman; Ihab Ahmed Ra'Uf Awais (UPM Press,Universiti Putra Malaysia 43400 UPM Serd, 2024)
Non-Indexed Publication